Comparative study of heart rate variability in normotensive young adults with family history of hypertension - Wadoo, Ovais K.; Sayeed, Sheikh I.; Tramboo, Mariya R. (International Journal of Research in Medical Sciences, 2021)
Background: Hypertension is a risk factor for the development of cardiovascular and cerebro-vascular diseases. Autonomic nervous system plays a crucial role in the development of hypertension. The integrity of autonomic modulation of heart rate is evaluated by analysing heart rate variability (HRV), which refers to oscillations in the intervals between consecutive heartbeats or R-R intervals. The present study was designed to analyse the indices of heart rate variability in the offsprings of hypertensive parents and off springs of normotensive parents to understand if there is any autonomic imbalance between the two groups. Methods: The study was conducted in the Department of Physiology, Government Medical College, Srinagar. The test group consisted of 30 healthy normotensive subjects studying in 1st year of MBBS with hypertensive parents and the control group consisted of healthy normotensive of 1st year of MBBS with both parents normotensive. In time domain analysis the standard deviation of all normal-to-normal intervals SDNN(ms) was taken as index of overall HRV. Frequency domain analysis was done with respect to low frequency (LF) analysis and high frequency (HF) analysis. Low and high frequency power were expressed in normalized units. Results: The SDNN was reduced in cases but was not statistically significant. RMSSD was also reduced in cases though not statistically significant. LFnu was found to be significantly higher in cases. The HFnu was significantly reduced in cases. LF/HF ratio was found to be higher in cases and the difference was statistically significant. Conclusions: Our study reveals that incidence of prehypertension and the risk of cardiovascular dysfunction in relation to sympathovagal imbalance is more in the off springs of hypertensive parents than in the off springs of normotensive parents. Sympathovagal imbalance in the form of increased sympathetic drive and decreased parasympathetic drive can lead to prehypertension in these genetically predisposed individuals.